2011
DOI: 10.1515/ans-2011-0106
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Joins and Weighted Barycenters

Abstract: Abstract. Given a space X, we study the homotopy type of Bn(X) the space obtained as the "union of all (n − 1)-simplexes spanned by points in X" or the space of "formal barycenters of weight n or less" of X. This is a space encountered in non-linear analysis under the name of space of barycenters or in differential geometry in the case n = 2 as the space of chords. We first relate this space to a more familiar symmetric join construction and then determine its stable homotopy type in terms of the symmetric pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…We have already indicated that Q n,k ≃ B n−1 (R k , n). On the other hand, according to Theorems 1.1, 1.3 and 1.5 of [16], we have that…”
Section: Lemma 41 Let X Be Path-connected Which Is Not a Point Locmentioning
confidence: 88%
See 1 more Smart Citation
“…We have already indicated that Q n,k ≃ B n−1 (R k , n). On the other hand, according to Theorems 1.1, 1.3 and 1.5 of [16], we have that…”
Section: Lemma 41 Let X Be Path-connected Which Is Not a Point Locmentioning
confidence: 88%
“…The case k = 1 is trivial. We let k ≥ 2 and invoke some main results from [16,17]. Let S be the unit sphere as in Lemma 2.2 and let Q n,k be its quotient under the S n -action.…”
Section: Lemma 41 Let X Be Path-connected Which Is Not a Point Locmentioning
confidence: 99%
“…Assuming by contradiction that α ρ ≤ − L 2 , there would exist a map π ∈ Π Φ with supσ ∈Km II(π(σ)) ≤ − 3 8 L. Then, since Proposition 2.7 applies with L 4 , writingσ = (σ, t), with σ ∈ Σ m , the map t → Ψ m • π(·, t) would be an homotopy in Σ m between Ψ m • Φ and a constant map. But this is impossible since Σ m is non-contractible (see [27]) and since Ψ m • Φ is homotopic to the identity on Σ m , by Proposition 2.8. Therefore, we deduce α ρ > − L 2 .…”
Section: Lemma 29mentioning
confidence: 99%
“…Remark 3.6 Since each γ i is topologically a circle, it follows from Proposition 3.2 in [10] that (γ 1 ) k (S 1 ) k is homeomorphic to S 2k−1 and (γ 2 ) l to S 2l−1 (in [27] it was proved previously a homotopy equivalence). As it is well-known, the topological join S m * S n is homeomorphic to S m+n+1 (see for example [23]), and therefore (γ 1 ) k * (γ 2 ) l is homeomorphic to the sphere S 2k+2l−1 .…”
mentioning
confidence: 98%
See 1 more Smart Citation